2020
DOI: 10.4102/sajems.v23i1.3028
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance, job satisfaction and retention: Turnover intentions of professionals in part-time study

Abstract: Background: Undertaking degree studies while working can provide life-changing career opportunities. These studies, however, can introduce substantial work-life balance conflict, particularly for those with family responsibilities, with important implications for retention.Aim: The aim of this study is to test theory that predicts the effects of certain moderating and mediated influences on the relationship between work-life balance conflict and turnover intentions of professional staff undertaking evening deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
2
10
0
3
Order By: Relevance
“…The H1 of this study was that work-life balance positively affects employee retention. The finding was supported, and therefore aligned to that of Kamalaveni et al ( 2019 ), Adriano and Callaghan ( 2020 ) and Choi ( 2020 ). Work- life balance appears to be an important component of corporate social responsibility, and results show that organizational leaders should be aware of their responsibilities to ensure that their staff are not working so hard that it interferes with their personal lives, as this may create medical concerns, and in turn affect morale, productivity, and job satisfaction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The H1 of this study was that work-life balance positively affects employee retention. The finding was supported, and therefore aligned to that of Kamalaveni et al ( 2019 ), Adriano and Callaghan ( 2020 ) and Choi ( 2020 ). Work- life balance appears to be an important component of corporate social responsibility, and results show that organizational leaders should be aware of their responsibilities to ensure that their staff are not working so hard that it interferes with their personal lives, as this may create medical concerns, and in turn affect morale, productivity, and job satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Hashim et al ( 2016 ) reported a high quality and direct relationship between work-life balance and retention among middle management employees in Malaysia. Additionally, research by Adriano and Callaghan ( 2020 ) on professionals in part-time study in South Africa showed that a favorable work-life balance could help to improve job satisfaction and employee overall turnover intention. Therefore, we hypothesized that:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Hal tersebut konsisten dengan studi yang meneliti pada 550 responden di industri manufaktur keramik di India yang diteliti oleh Umamaheswari et al (2015) mengindikasikan adanya korelasi positif antara pelaksanaan work-life balance dengan tingkat retensi karyawan. Studi yang dilakukan oleh Adriano & Callaghan (2020) juga menemukan bahwa perusahaan sebaiknya mempunyai regulasi worklife balance yang dapat mengakomodasi adanya dampak dari konflik work-life, sehingga dapat membantu organisasi dalam meretensi karyawannya. Uraian di atas menjadi dasar untuk mengajukan hipotesis sebagai berikut: H2: Work-Life Balance berpengaruh terhadap Retensi Karyawan.…”
Section: Hubungan Work-life Balance Dan Retensi Karyawanunclassified
“…As a result, Industrial & Organisational (I/O) Psychologists need to master the science of retaining valued employees as they immensely contribute to the organisation's success. However, looking at previous studies, more research is on why employees choose to leave educational industry (Adriano & Callaghan, 2020;Barkenhuizen et al, 2020;Chacha et al, 2019;Mashile et al, 2021;Sender et al, 2018), rather than why employees stay within the organisation…”
Section: Literature Reviewmentioning
confidence: 99%